The effect of shock and regular probation upon recidivism: A comparative analysis - Vito, Gennaro F. (American journal of criminal justice, 1985)
Previous studies of shock probation have reported mixed effects with regard to recidivism rates. This particular study compared the attributes of a sample of shock and regular probationers and discovered that type of probation was not significantly related to rearrest rates.